PEMBERDAYAAN REMAJA SEBAGAI GENERASI PENCEGAHAN HIV/AIDS MELALUI APLIKASI DETEKSI DINI “PAHIVA” - Maulidiyah Salim; Tessa Siswina; Elma Marsita (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
HIV/AIDS cases in Indonesia remain high, particularly among adolescents. Limited knowledge and the perception that HIV/AIDS is a taboo topic make adolescents vulnerable to risky behaviors. This community service activity aimed to improve adolescents’ knowledge about HIV/AIDS and to introduce the Pantau HIV/AIDS (PAHIVA) application as an Android-based early detection tool. The implementation methods included preparation (coordination, permission, and material development), implementation (health education and PAHIVA application introduction), and evaluation (pre-test and post-test). The activity was carried out at SMA Negeri 6 Singkawang Utara, involving 40 participants consisting of students, guidance counselors, and the school principal. The Wilcoxon test showed a significant increase in students’ knowledge, with a median pre-test score of 72 (53–87) and a post-test score of 86 (67–100), p = 0.002. The program’s outputs included mass media publication, video documentation, and educational pamphlets. These results indicate that digital application-based health education is effective in improving adolescents’ literacy about HIV/AIDS. This activity is expected to serve as a promotive-preventive education model that can be sustained through peer group strengthening and collaboration between schools and health facilities.